Antibacterial Activity of Lemongrass (Cymbopogon citratus) Against Staphylococcus aureus in Cellulose Nanofibers from Lignocellulosic Biomass and Glycerol - Firdaus Flora Elvistia; Calluna Bunga Fatimatuzzahra; Nasution Siti Khodijah (BIO Web of Conferences)
Lemongrass oil (LGO) has great antimicrobial effects, it increases shelf life as a food coating. Incorporating LGO into cellulose nanofibres (CNFs)-(Glycerol)-(Starch) was done by a mixing procedure and the antibacterial characteristics were evaluated. The interaction of LGO in the composite systems was studied by Scanning electron microscopy (SEM), microbial analysis by total plate count, antimicrobial by inhibitory zone, film thickness, and by the support of Fourier-transform infrared spectroscopy (FT-IR). The results indicated that the best composite systems could maintain LGO by 0.15 g at all predetermined cellulose concentrations. Its antibacterial substance can be integrated into a polymer matrix for active coating.